Effects of Auxiliary Chemicals on the Ozonation of Industrial Dyes - Rajeswary K, Ramasamy; Abd. Rahman, Noorsaadah; C.S, Wong; Bakar N.K, Abu (Malaysian Journal of Science, 2005)
The effect of commonly used auxiliary chemicals (primasol, sodium hydroxide and sodium hydrosulphite) and the initial dye concentration on the oxidation of three industrial dyes (Vat Blue, Disperse Blue 79 and Disperse Red 72) has been studied. In the batch studies, the oxidation of dye molecules by ozone was examined with single-solute dye solution. Our results showed that the efficiencies of dye removal were in the range 68-74% and 80-85% at an oxidation time of 10 minutes and 2 hours respectively. The effect of each of the three auxiliaries on the single- and multi-solute dye solutions were assessed in terms of colour, COD and TOC variation. The addition of primasol showed exertion on ozone demand as reflected by the COD and TOC results while sodium hydroxide enhanced the oxidation of Disperse Blue 79. The presence of sodium hydroxide also reduced the colour removal and the reduction of COD in the oxidation of Vat Blue dye as well as the mixture of three dyes studied. Sodium hydrosulphite being a strong reducing agent exerted a significant demand on ozone, reducing amount of ozone available to oxidize the dye molecules.